Challenges in Advocating for Smoke-Free Zones (SFZs): A Literature Review of Tobacco Industry Interventions - Irfan Sazali Nasution; Satia Redha; Dafina Hilya Fatiha Ginting; Ririn Hasrat Kartika Zalukhu; Siti Hajar Lubis; Janny Aulia Sari Hasibuan; Restu Rahayani Padang (Universitas Muhammadiyah Palu, 2026)
Abstract This study aims to systematically identify, analyze, and synthesize various research findings related to the challenges of policy advocacy for Smoke-Free Zones (SNOZs) and tobacco industry interventions in Indonesia. Using a systematic literature review method, a comprehensive literature search was conducted through international and national databases including PubMed, Google Scholar, and Science Direct. Based on strict inclusion and exclusion criteria, a sample of 12 primary articles published between 2020 and 2025, using descriptive qualitative designs, case studies, implementation research, and literature reviews, was selected through a multistep screening process. The main issues and variables examined in this study include structural barriers of local governments, community compliance, cross-sector coordination, political lobbying, corporate social responsibility (CSR) initiatives, and point-of-sale marketing. The results indicate that advocacy and implementation of SNOZs in Indonesia are severely hampered by incomplete communication, limited budgets and institutional resources, and a widespread smoking culture. Furthermore, tobacco industry interventions actively undermine these public health variables by promoting weaker alternative regulatory frameworks (such as indoor smoking spaces instead of total bans), exploiting weak law enforcement coordination, and targeting young people through intensive retail advertising around educational areas.